Eponyms have no place in 21st-century biological nomenclature - Guedes Patrícia; Alves-Martins Fernanda; Arribas Javier Martínez; Chatterjee Sumita; Santos Ana MC; Lewin Amir; Bako Longji; Webala Paul W; Correia Ricardo A; Rocha Ricardo; Ladle Richard J (Nature Portfolio, 2025)
We argue that naming species in honour of a specific person is unjustifiable and out of step with equality and representation. Reforming taxonomy to remove eponyms will not be easy but could bring multiple benefits for both conservation and society.